CUSTOMER PERCEPTION; E-WALLET USED AS A NON-CASH PAYMENT TOOL - Salsabilla Aulia Az Zahrah; Leonard Adrie Manafe; Titis Tatasari; Mochamad Fatchurrohman; Fajar Tenovita Sari (STIE Mahardhika, 2023)
This study aims to determine customer perceptions of Haus! Siwalankerto regarding the use of e-wallets as non-cash payments. The method used in this study is a qualitative method with excavation techniques through interviews. Retrieval of data in this study using informants as many as seven customers. This research provides valuable insights for stakeholders, including e-wallet companies, merchants, and local governments, in increasing e-wallet adoption in Haus! Siwalankerto. The indicators used to see perceptions are perceptions of convenience, usability and risk. This research shows that: First, Perceived Convenience, most customers agree that e-wallets provide many conveniences; Second, Perceived Usefulness shows that the majority of customers agree that during payment transactions they use e-wallets; Third, Risk Perception shows that a small proportion agree that e-wallet payments are very low risk. Research show, it can be seen from the large number of customer interests, it shows that almost all use e-wallet payments as a non-cash payment instrument. Then the use of e-wallets on Haus! Siwalanketo is influenced by these three perceptions.